(untitled)
This paper defines a new class of graphs using the spanning subgraphs of a cycle graph as vertices. This class of graphs is called j-edge intersection graph of cycle graph, denoted by E_C_(n,j) . The vertex set of E_C_(n,j) is the set of spanning subgraphs of cycle graph with j edges where n ≥ 3 and j is a nonnegative integer such that 1 ≤ j ≤ n. Moreover, two distinct vertices are adjacent if they have exactly one edge in common. E_C_(n,j) is considered as a simple graph. Furthermore, E_C_(n,j) is characterized by the value of j that is when j=1 or n2 ceil < j ≤ n and 2 ≤ j ≤ n2 ceil. When j=1 or n2 ceil < j ≤ n, the new graph only produced an empty graph. Hence, the proponents only considered the value when 2 ≤ j ≤ n2 ceil in determining the order and size of E_C_(n,j) . Moreover, this paper discusses necessary and sufficient conditions where the j-edge intersection graph of C_n is isomorphic to the cycle graph. Furthermore, the researchers determined a lower bound for the independence number, and an upper bound for the domination number of E_C_(n,j) when j=2. , number=4, journal=European Journal of Pure and Applied Mathematics, year=2023, month=Oct., pages=2476–2498